2002
DOI: 10.1152/ajpheart.00021.2002
|View full text |Cite
|
Sign up to set email alerts
|

PYK2 expression and phosphorylation increases in pressure overload-induced left ventricular hypertrophy

Abstract: Proline-rich tyrosine kinase 2 (PYK2) is a member of the focal adhesion kinase (FAK) family of nonreceptor protein tyrosine kinases. PYK2 has been implicated in linking G protein-coupled receptors to activation of mitogen-activated protein kinase cascades and cellular growth in a variety of cell types. To determine whether PYK2 expression and phosphorylation is altered in left ventricular (LV) myocardium undergoing LV hypertrophy (LVH) and heart failure in vivo, suprarenal abdominal aortic coarctation was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 38 publications
(76 reference statements)
2
35
0
1
Order By: Relevance
“…RAFTK/pyk2 concentration in cardiomyocytes is much greater in neonates than adults and is highly dependent on calcium transients and contractility (26). Consistent with our findings in the pathologically altered myocardium (7), increased expression and phosphorylation of RAFTK/pyk2 were noted following left ventricular hypertrophy induced by pressure overload (28). We found overexpression of WT RAFTK/pyk2 caused dramatic changes in myofibril organization consistent with a role in reorganization of focal adhesions and cytoskeleton and demonstrated that RAFTK/pyk2 is activated in dilated cardiomyopathy (7).…”
supporting
confidence: 86%
“…RAFTK/pyk2 concentration in cardiomyocytes is much greater in neonates than adults and is highly dependent on calcium transients and contractility (26). Consistent with our findings in the pathologically altered myocardium (7), increased expression and phosphorylation of RAFTK/pyk2 were noted following left ventricular hypertrophy induced by pressure overload (28). We found overexpression of WT RAFTK/pyk2 caused dramatic changes in myofibril organization consistent with a role in reorganization of focal adhesions and cytoskeleton and demonstrated that RAFTK/pyk2 is activated in dilated cardiomyopathy (7).…”
supporting
confidence: 86%
“…The Ca 2+ -dependent, nonreceptor protein tyrosine kinase PYK2 has been previously implicated in cardiomyocyte cell signaling pathways leading to LVH and HF (2)(3)(4)(5)(6). PYK2 is a member of the focal adhesion kinase (FAK) family of nonreceptor PTKs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in this field indicate that the integrity of structures such as the Z disk, costamere, and intercalated disk is critically important to the ability of cardiac cells to appropriately respond to mechanical stress (4,11,21,32,37,41). It has been hypothesized that such structures participate in monitoring of mechanical force and in communication of strain to signaling molecules in cardiac myocytes (12,29,37).Focal adhesion kinase (FAK), a tyrosine kinase linked to integrin signaling (15,24,42), has been shown to be rapidly activated by mechanical stimuli in cardiac myocytes (2,5,9,12,13,23,34,39). Several lines of evidence support a role for FAK in the regulation of early gene transcription in response to hypertrophic agonists and mechanical stress (10,22,28,38,39), indicating that this kinase may coordinate the convergence of multiple signaling pathways involved in the hypertrophic growth of cardiac myocytes.…”
mentioning
confidence: 99%
“…Focal adhesion kinase (FAK), a tyrosine kinase linked to integrin signaling (15,24,42), has been shown to be rapidly activated by mechanical stimuli in cardiac myocytes (2,5,9,12,13,23,34,39). Several lines of evidence support a role for FAK in the regulation of early gene transcription in response to hypertrophic agonists and mechanical stress (10,22,28,38,39), indicating that this kinase may coordinate the convergence of multiple signaling pathways involved in the hypertrophic growth of cardiac myocytes.…”
mentioning
confidence: 99%